BOOKTAXDIFFERENCESINLARGETRADINGSUB-SECTORCOMPANIES - Ilmiyono, Agung Fajar; Indrayono, Yohanes; Hurriyaturrohman, Hurriyaturrohman; Salsabila, Sharah (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Taxes play a very important role as a source of state revenue. The existence of corporate obligations as corporate taxpayers results in the implementation of bookkeeping compiled based on General Provisions and Tax Procedures. The purpose of this study is (1) To explain the application of PSAK 46 regarding income tax accounting in large trading subsector companies listed on the Indonesia Stock Exchange. (2) To explain the application of the income tax laws to large trading subsector companies listed on the Indonesia Stock Exchange. (3) To explain the differences between commercial profits and fiscal profits after a fiscal reconciliation (correction) is made to a large trading subsector company listed on the Indonesia Stock Exchange (4) To explain the comparison of compliance rates of large trading sub-sectors listed on the Indonesia Stock Exchange in 2016 -2018 in the Income Tax ActThis research was conducted on large trading sub-sector companies listed on the Indonesia Stock Exchange in 2016 -2018. Samples used in this study were 6 companies. Samples were selected using the purposive sampling method. The analytical method used in this research is descriptive non statistic which functions as an analyzer of the collected data.The results of the study show that in the large trading sub-sector companies that have been analyzed, there are parts of deductible expenses to be used as non-deductible expenses, there is a lot of reserve fund fertilization so that it cannot reduce fiscal profit and there are companiesthat have participated in tax amnesty so that they get a profit on tax that should be owed. Related to the phenomena presented in the background of the study, the tax revenue from the wholesale trade sub-sector is not only from Income Tax Article 22 Imports, but from aspects of costs that cannot reduce fiscal profits (nondeductible expenses) included in Article 9 of the Tax Law Income so that the more costs that cannot be reduced in fiscal profit, the greater the tax burden owed. After a comparison, the fiscal reconciliation of PT Lautan Luas Tbk is a company that meets the Income Tax Act regulations.